The influence of occupations on the complex program of physical rehabilitation on the bioelectric activity of heart of adolescents with bronchial asthma - Furman Yuriy; Оnyschuk Victoria; Gavrilova Natalia; Zdebskі Alexandr (Kharkiv State Academy of Physical Culture, 2019)
Over the last decade medical statistics have shown a steady increase of bronchial asthma among people of all ages. In Ukraine, 8,1% of 6-7 years old children have bronchial asthma; at the age of 16-18 years - 6.1%. This percentage of morbidity among young people is not only a biomedical, but also a social problem, as it creates obstacles in education and further restricts the opportunity to choose a profession. It is worth noticing, that the prevalence of asthma is accompanied by a complication of the disease. It is known that people with bronchial asthma often have abnormalities of the cardiovascular function. Such people are inclined to have sinus tachycardia with more than 120 contractions in 1 minute, an increase in blood pressure, an increase in clinical signs of right ventricular insufficiency (swelling of the cervical veins, enlargement of the liver). With the help of an electrocardiogram the signs of an overload of right departments of heart are determined. Such consequences cause concerns, which further can lead to disability and mortality. Various means of physical rehabilitation are used to improve the condition of patients with bronchial asthma. However, the use of traditional methods and means of physical rehabilitation are not always effective for patients, as evidenced by the increase in the incidence rate among young people. Classical means of physical rehabilitation are used mainly in sanatorium-medical and dispensary establishments, which makes them inaccessible for young people during the period of studying, because they are run out of time. These facts raise the problem of finding and developing new effective technologies for the physical rehabilitation of youngpeoplesufferingfrom bronchialasthma. The purpose of the work is to substantiate and develop a comprehensive program of physical rehabilitation of adolescents with bronchial asthma. Research methods. The following research methods were used to solve these tasks: review of literary sources; electrocardiography, sphygmomanometry; methods of mathematical statistics. Results. The developed program exercises, which included respiratory gymnastics on the apparatus "Endogenic 01", did not cause negative changes in the bioelectric activity of the adolescents' hearts. The results of our studies showed that under the influence of systematic classes in students of the main group, after 30 weeks, the duration of the R-R interval increased by 3,67% (p <0,05). In this case, the heart rate is reduced by 3,18% (p<0,05). After completing the course of physical rehabilitation, we registered a furtherincrease in the R-R interval (by 3,79%, p<0,05)in the students of the main group. The heart rate in adolescents by 3,42% (p <0,02) remained significantly lower compared to the values recorded prior to the formation of the experiment. The rest of the studied indicators of adolescents heart's bioelectric activity did not change significantly during the 40 weeks of training. We have not registered any significant changes in blood pressure in the students of this group during the 40-week training period. Conclusions. Classes of the developed program did not cause negative changes in the bioelectric activity of the heart in adolescents. At the same time, it should be noted as a positive phenomenon that a reliable decrease in heart rate indicates the economization of cardiac activity of the subjects studied in a state of a relative muscle rest.